The Influence of Principal Supervision and Pedagogic Competence On Teacher Innovativeness and Teacher Work Quality - Mulyadi; Ali, Hapzi; Imron Rosadi, Kemas (International Journal of Advanced Multidisciplinary, 2023)
Teacher Work Quality is an individual's feelings and perceptions about the balance of personal life and professional life in relation to work, co-workers and the organization where he works. The Effect of Principal Supervision, and Pedagogic Competence on Teacher Innovativeness and the Quality of Teacher Work is a scientific article of literature study within the scope of the field of science. The purpose of this article is to build a hypothesis of the influence between variables that will be used in further research. Research objects in online libraries, Google Scholar, Mendeley and other academic online media. The research method with the research library comes from e-books and open access e-journals. Qualitative descriptive analysis. The results of this article: Principal Supervision (X1) and Pedagogic Competence (X2) on Teacher innovation (Y1) and Teacher work quality (Y2).